2004
DOI: 10.1213/01.ane.0000096002.53818.bd
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Randomized Crossover Trial of the N-Methyl-d-Aspartic Acid Receptor Antagonist, Memantine, in Patients with Chronic Phantom Limb Pain

Abstract: NMDA receptors play a substantial role in central nervous system changes underlying neuropathic pain. In a placebo-controlled double-blinded study we tested the effect of 30 mg memantine on chronic phantom limb pain and pain-associated cortical reorganization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 42 publications
1
57
0
4
Order By: Relevance
“…Although it could theoretically possess some analgesic properties, controlled trials published so far have been disappointing [90,91].…”
Section: N-methyl-d-aspartate Receptor Blockersmentioning
confidence: 99%
“…Although it could theoretically possess some analgesic properties, controlled trials published so far have been disappointing [90,91].…”
Section: N-methyl-d-aspartate Receptor Blockersmentioning
confidence: 99%
“…Previous studies on the treatment of phantom limb pain with Memantine reported normalization of cortical reorganization: displaced or enlarged somatotopic representation of the painful limb was successfully reversed after treatment. 19,20 There is increasing evidence that cortical reorganization is causally involved in the maintenance of chronic neuropathic pain. 21,22 The aim of this study was to demonstrate a CNS contribution in the development and preservation of CRPS.…”
mentioning
confidence: 99%
“…Entre sus indicaciones se han propuesto: dolor neuropático oncológico, neuralgia postherpética, traumatismo crónico, amputación, lesión de la ME, dolor de origen central secundario a accidente cerebrovascular, dolor de miembro fantasma, síndrome de piernas inquietas, dolor crónico orofacial, fibromialgia y dolor postquirúrgico, entre otros (13,23,24,30,31).…”
Section: Indicacionesunclassified